Metal, dielectric and hybrid nanoantennas for enhancing the emission of single quantum dots: A comparative study. (December 2021) - Barreda, A.; Hell, S.; Weissflog, M.A.; Minovich, A.; Pertsch, T.; Staude, I.
Highlights: A hybrid metal-dielectric antenna boosted the performance of single-photon sources. A gold dimer constituted by cylinders provided large Purcell factor values. Quadrupolar electric resonance excitation in the gold dimer provided directionality. Silicon directors further improved the directivity. Abstract: The confinement of electromagnetic energy to subwavelength volumes through nanoscale antennas can be used to enhance the spontaneous emission of quantum emitters. With this aim, different configurations of metallic and high refractive index dielectric nanoparticles have been explored. Here, we carry out a comparative analysis of planar metallic, high refractive index dielectric, and hybrid nanoantennas considering three different parameters: the Purcell factor enhancement, radiation efficiency, and directionality properties. We focus our study on different geometries and material combinations of a dimer of cylinders. A dimer made of two gold nanocylinders is the most promising candidate for improving the spontaneous emission. While most previous works have paid attention to the redirection of the scattered emission in the nanoparticle plane, our proposed nanostructure of two large gold cylinders ( R = λ / 4 ) emits most of the radiation upwards. This effect is due to the strong quadrupolar electric contribution to the resonant mode. With the aim to further improve the directionality properties, additional silicon nanocylinders are used as directors of the scattered radiation, increasing the directivity by a factor of 2.4 with respect to the gold dimer without directors. All in all, a hybrid structure composed of a gold dimer and silicon nanoparticles is proposed to enhance the spontaneous emission of a single quantum dot and to govern its emission pattern. The results shown in this work could be useful in fluorescence enhancement or in quantum photonics. They are particularly interesting for the development of single-photon sources based on quantum dots and other nanoscale emitters.